Analysis of the Clap Method as an Recognition Strategy Mathematics Numeration in Autism Students at Special Needs School - Yeanny Suryadi; Dian Armanto (research, training and philanthropy institution Natural Aceh, 2023)
Many interventions are done by parents to build some stimulation for their autistic children. Various stimulation techniques and models are created to stimulate the development of the brain, which is related to the ability to achieve the intended educational achievements. The most important hope of parents for their autistic children is the ability for them to live independently in the future, that is why early interventions need to be done, including educating their children via particular institution unit, such as special needs school, which contains in addition to academic subjects as well as non-academic ones that have been adapted according to the needs of the students. Mathematics is one of the subjects needed by students in general and students with disabilities in particular as a basis for growth in their logical thinking development, which is essential for their future. This research lasted for two months, with a qualitative study focusing on 20 students in Special Needs School at Deli Serdang; in the end, the conclusion is that the clapping technique for introduction numbers in A and B classes works. Students can sequence numbers well enough and know about the symbols of numbers.